Premature Ventricular Contractions From the Left Anterior Fascicle: Electrocardiographic and Electrophysiological Characteristics, Mapping Strategy, and Immediate and Long-Term Catheter Ablation Results - Chen, Hongwu; Xiao, Fangyi; Ju, Weizhu; Yang, Gang; Zhang, Fengxiang; Gu, Kai; Li, Mingfang; Liu, Hailei; Wang, Zidun; Sharma, Dinesh; Cao, Kejiang; Chen, Minglong (Frontiers in Cardiovascular Medicine, 2022)
Background Left anterior fascicle (LAF) premature ventricular contractions (PVC) are rarely reported. We described the electrocardiographic and electrophysiological characteristics of PVCs originating from LAF and evaluated the results of catheter ablation. Methods The baseline AH and HV intervals were recorded during normal sinus rhythm (NSR), and the HV interval of LAF-PVC was measured during the procedure. During the index procedure, the conduction interval from the earliest Purkinje potential (PP) site to the His was labeled as time A, the conduction interval from the earliest site to the onset of the QRS as time B, then the HV interval during NSR (HVNSR) is A + B, and the HV interval during PVC (HVPVC) is B-A; a predicted PP time was calculated using HVNSR and HVPVC. The calculated formula is as follows: Predicted target PP = (HVNSR + HVPVC)/2. During the repeat procedure, the mapping strategy only focuses on the earliest retrograde PP due to the injury or block of LAF sustained at the index procedure. Results Notably, 24 patients with LAF-PVC were included. The ECG characteristics of PVC exhibited right bundle branch block (RBBB) morphology with right-axis deviation (RAD) in 18 patients and only RAD in 6 patients. The QRS durations of NSR and PVC were 78.8 ± 7.9 and 106.8 ± 12.3 ms, respectively. There was no significant difference between the predicted and mapped PP site (31.5 ± 8.1 vs. 30.6 ± 7.8 ms; P = 0.17). There was a significant difference between the mean axis deviation before and after ablation (46.3 ± 25.4° vs. 18.3 ± 44.1°; P = 0.001); however, only 10 patients had a complete LAF block. Eight patients had a recurrence, the QRS morphology of LAF-PVC became narrower (95.9 ± 17.2 vs. 105.3 ± 16.9 ms, P = 0.003), and 4 patients’s PVC QRS morphology was similar to NSR. During the repeat procedure, the earliest retrograde PP interval was longer than the index procedure in four patients (12.0 ± 1.9 vs. 37.8 ± 1.1 ms; P < 0.001). Conclusion The target PP site for ablation of the LAF region can be calculated using the HV interval during NSR and PVC at the index procedure. The mapping strategy at repeat procedures focused on the earliest retrograde PP interval.